Effectiveness of Neuro Developmental Treatment (NDT) For Treating Cerebral Palsy Children - A Systematic Review - Malawade, Mandar; G. Varadharajulu, G. Varadharajulu (Journal of Neonatal Surgery, 2025)
Background: Neurodevelopmental Treatment (NDT) is a widely adopted intervention for children with cerebral palsy (CP), aiming to improve motor function and overall development. Despite its extensive use, the comparative efficacy of NDT against alternative therapies remains inconclusive. Objective: This systematic review aims to evaluate the effectiveness of NDT in improving motor function and other developmental outcomes in children with CP by analyzing available literature. Methods: A comprehensive review of clinical trials assessing the outcomes of NDT was conducted. Data from multiple studies were synthesized to compare NDT outcomes with alternative interventions. Outcome measures included GMFM-66, GMFM-88, Mechanical Efficiency Index, and passive range of motion (ROM). Results: Findings demonstrated that NDT effectively improved gross motor function in children with CP. Studies indicated enhanced outcomes in "Lying & Rolling" and "Standing" when compared to SIT. Intensive NDT protocols showed greater improvements than standard protocols. Additionally, combining NDT with complementary techniques such as Electrical Stimulation or Joint Position Sense Training further enhanced functional outcomes. However, improvements in specific domains such as social-emotional, language, and cognitive development were inconclusive. Conclusion: While NDT offers measurable improvements in motor function, evidence remains insufficient to confirm its superiority over alternative interventions. Future studies should employ larger sample sizes, homogeneous participant groups, and clearly defined treatment protocols to enhance the robustness of findings.